S2k-Leitlinie der PEG zur kalkulierten parenteralen Initialtherapie bakterieller Erkrankungen bei Erwachsenen: fokussierte Zusammenfassung und ergänzende Informationen zur Antibiotikatherapie kritisch kranker Patienten = S2k guidelines of the PEG on calculated parenteral initialtreatment of bacterial diseases in adults : focussed summary andsupplementary information on antibiotic treatment of critically ill patients - Brinkmann, Alexander; Brenner, Thorsten; Richter, Daniel (Der Anaesthesist, 2018)
In January 2018 the recent revision of the S2k guidelines on calculated parenteral initial treatment of bacterial diseases in adults—update 2018 (Editor: Paul Ehrlich Society for Chemotherapy, PEG) was realized. It is a helpful tool for the complex infectious disease setting in an intensive care unit. The present summary of the guidelines focuses on the topics of anti-infective agents, including new substances, pharmacokinetics and pharmacodynamics as well as on microbiology, resistance development and recommendations for calculated drug therapy in septic patients. As in past revisions the recent resistance situation and results of new clinical studies are considered and anti-infective agents are summarized in a table.